Adipose Tissue Biology: An Update Review - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Obesity is a major health problem in most countries in the world today. It increases the risk of diabetes, heart disease, fatty liver and some form of cancer. Adipose tissue biology is currently one of the “hot” areas of biomedical science, as fundamental for the development of novel therapeutics for obesity and its related disorders.CONTENT: Adipose tissue consist predominantly of adipocytes, adipose-derived stromal cells (ASCs), vascular endothelial cells, pericytes, fibroblast, macrophages, and extracellular matrix. Adipose tissue metabolism is extremely dynamic, and the supply of and removal of substrates in the blood is acutely regulated according to the nutritional state. Adipose tissue possesses the ability to a very large extent to modulate its own metabolic activities including differentiation of new adipocytes and production of blood vessels as necessary to accommodate increasing fat stores. At the same time, adipocytes signal to other tissue to regulate their energy metabolism in accordance with the body's nutritional state. Ultimately adipocyte fat stores have to match the body's overall surplus or deficit of energy. Obesity causes adipose tissue dysfunction and results in obesity-related disorders.SUMMARY: It is now clear that adipose tissue is a complex and highly active metabolic and endocrine organ. Undestanding the molecular mechanisms underlying obesity and its associated disease cluster is also of great significance as the need for new and more effective therapeutic strategies is more urgent than ever. KEYWORDS: Obesity, Adipocyte, Adipose, Tissue, Adipogenesis, Angiogenesis, Lipid Droplet, Lipolysis, Plasticity, Dysfunction